QUANTITATIVE ICP-MS ASSESSMENT OF TRACE METAL DIETARY RISK AND MARGIN OF EXPOSURE IN PROTEIN POWDERS FROM DIVERSE SOURCES: - C A SRI RANJANI; C ASHA DEEPTI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study aimed to determine the concentration levels of harmful heavy metals – arsenic (As), cadmium (Cd), lead (Pb), and mercury (Hg) – in commercially available whey and vegan protein powders sourced from India, China, and Japan, and to assess the potential non-carcinogenic health risks associated with their consumption based on target hazard quotient (THQ) and hazard index (HI) values. The reliability and efficiency of the analytical method employed for trace metal determination were also evaluated. Methods: Quantitative analysis of As, Cd, Pb, and Hg was performed on whey and vegan protein powder samples using microwave-aided acid digestion, followed by an analytical technique using ICP-MS, daily intake estimations, THQ, and HI were calculated to assess potential non-carcinogenic health risks. Results: Heavy metals were detected in protein powder samples, posing potential health risks. On-carcinogenic risk, measured by hazard quotient (HQ), is concerning if > 1, based on estimated daily intake (EDI) and compared to provisional tolerable daily intake (PTDI). Non-carcinogenic metal transfer percentages are 14% (copper, lead, cadmium), 24% (mercury), and 35% (arsenic). A hazard index (HI) > 1 indicates cumulative risk. Carcinogenic risk is unacceptable if > 10⁻6, calculated using slope factors (SF₀) such as 1.5 (arsenic) and 0.0085 (lead) (mg kg⁻1 day⁻1 bw)⁻ 1. The analytical method used was reliable for trace metal detection in these samples. Conclusion: The presence of heavy metals in commercially available protein powders and the associated potential non-carcinogenic health risks, as indicated by THQ and HI values, underscores the need for stringent quality control measures within the protein supplement industry. The validated analytical method provides a useful tool for future monitoring and risk assessment in this domain